PENGARUH MEDIA PEMBELAJARAN TEKNOLOGI APLIKASI GAME EDUCANDY TERHADAP KETERTARIKAN PEMBELAJARAN BAHASA INGGRIS SISWA KELAS 5 (Studi Kasus Pada Madrasah Ibtidaiyah Swasta Ma’had Al-Zaytun Indramayu) - Elvira Jahrotul Aina; Irvan Iswandi; Dede Indra Setiabudi (STKIP Subang, 2024)
This research examines the influence of the Educandy application technology learning media on the interest in learning English of grade 5 students at MIS Ma'had Al-Zaytun. The aim of this research is to understand that there is an influence of Educandy learning media on the interest in learning English for grade 5 students and also to find out the level of interest in learning English with the use of Educandy learning media. This research method uses a quantitative approach with a pre-experimental research type. Data collection was carried out by conducting a pretest-posttest and giving questionnaires to class 5 students for the 2023/2024 academic year, who were the population of this study. The sample determination in this study was carried out using a purposive sampling technique, resulting in a sample size of 52 respondents. The results obtained when conducting this research were that there was an increase in the average test results in the pre-test and post-test until it reached 44. The number of valid questions in the pre-test, post-test and questionnaire was 10, 8 and 14 questions, respectively. while all instruments were declared reliable. The results of the questionnaire stated that the student interest rate was categorized as positive with a figure of 75.8%. The data in hypothesis testing was stated to be normally distributed and after being tested using the t test, H1 was accepted. Research shows that there is an influence of using Educandy learning media on students' interest in learning English and also the number of students' interest in learning English using Educandy learning media is in the high category Keywords: Learning Media, English, Interest in Learning;